Modeling of the corona ionization space propulsion system - Pokaha, Marius Tchonang (My University, 2011)
In this thesis, a novel type of electrostatic thruster is introduced. The Corona Ionization (CorIon) Space Propulsion system is an electrostatic propulsion system intended for use on satellites and for deep space probes. It makes use of the corona ionization mechanism to create the needed propellant ions. This same mechanism is also responsible for the thrust, thereby reducing its size and complexity. First, the effects of incomplete ionization of propellant molecules is discussed and conclusions drawn. Next, a mathematical model describing the electric field characteristics is derived. Considering the needle tip as a point charge and the exhaust plume to be cylindrically symmetric with a constant spread angle, the resultant electric field of both the needle tip and the produced ions obeys Poisson‘s equation. The charge density is obtained from the relationship between the drift velocity and the current. In order to solve the differential equation, we consider the electric field to only change in the radial direction so that Poisson‘s Equation is reduced to its radial part. This differential equation is solved to yield the electric field of the system. Some results are discussed. By integrating the electric field the relationship between the potential difference and the current of propellant ions is obtained. This relationship also yields insight into the ionization efficiency. Following this, an expression for the thrust is derived via two different methods: The first uses the energy conservation, and is termed ―Vector heating‖. The ions are viewed as a current heating the neutrals in the plume in the direction away from the needle. A temperature can be derived for the plume, and the resulting average gas velocity estimated from molecular theory. Finally, using the rocket thrust equation, an expression for the thrust is obtained. iv The second, more conventional method uses electrostatic repulsion to calculate the recoil on the needle: from the electric field computed for the system, an expression for the Coulomb forces on the ionized propellant can be derived. The recoil on the needle will experience the same force, resulting in thrust. Finally, the theoretical predictions for the various parameters are compared to experimental data. From this comparison, it is seen that there is a reasonable agreement between the experimental data and the model even though the electrostatic prediction underestimates the thrust of the system.
MSc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: ionization; corona (electricity)